Post-Contract Protection against Contracting Parties through Self-Help Remedies According to Islam and Laws Relating to Contracts - Haji Ahmad, Shofian (Kanun: Jurnal Undang-undang Malaysia, 2022)
The thought about protection of the contracting party does exist in Islam and the law because it is a necessity to give justice to the weaker party in the contract, such as the buyer. Recently, there are many cases involving fraud and exploitation towards the buyer and consumer in the sale of goods due to the imbalance of negotiating power between the two parties in the contract. Therefore, the effort to protect the weaker party in a contract is very appropriate and because it can give integrity to the sealed contract. Islamic scholars have outlined certain rules to protect contracting parties at the post-contract phase. Similarly, in the law related to contracts, there are various methods that can be used by the aggrieved party to claim their right to be honoured by the other party. Among the intended methods is self-help remedies. This article discusses the aspects of self-help remedies that can be claimed by the aggrieved party after the contract is executed based on Islam and the law. This study is that of a comparison by analyzing views from the perspectives of Islam and the law related to self-help remedies to protect and provide justice to the contracting weaker party. The results of this study found that there are some differences of opinion in terms of concepts and philosophy between Islam and modern contract law regarding the forms of self-help remedies. Some concepts of remedies found in Islam are not found in modern law. However, there are similarities in the general goal between Islam and modern contract law, which is to guarantee justice and the balance of negotiating power between the contracting parties. It is hoped that the findings of this study can contribute to the efforts to improve the protection of contracting parties in current times, which are increasingly complex and difficult. Keywords : Self-help remedies, post-contract protection, khiyar (options), cancellation of contract, right of return, Islamic view Full text : PDF